TIS11 AND CTH1 DEFICIENCY LEADS TO METABOLIC REPROGRAMING AND EXTENDS REPLICATIVE LIFESPAN IN YEAST. (11th November 2018) - Beaupere, C; Wasko, B; Kaeberlein, Matt; Labunskyy, V
Abstract: Iron (Fe) serves as a cofactor for many enzymes involved in metabolism and mitochondrial function. Dysregulation of Fe homeostasis has been implicated in the pathogenesis of numerous age-related human diseases. However, the role of Fe bioavailability in regulation of lifespan and how aging affects Fe homeostasis remain poorly understood. In the present study, we investigated the role of Tis11 and Cth1, two mRNA-binding proteins (RBP) involved in the cellular response to Fe deficiency, in lifespan regulation using yeast model. Our data demonstrate that deletion of TIS11 and CTH1 significantly extends replicative lifespan. Using a combination of RNA sequencing (RNA-Seq) and ribosome profiling (Ribo-Seq) we quantitatively analyzed translational changes in these deletion mutants. We show that increased lifespan in the tis11Δ and cth1Δ mutants is associated with activation of genes involved in regulation of Fe transport as well as Fe-containing proteins involved in mitochondrial respiration and amino acid metabolism. Moreover, we found that lifespan extension in the cth1Δ deletion mutant is dependent on the Gcn4 and Hac1 transcription factors, which was not observed in the tis11Δ cells. Together, our data suggest that iron deficiency caused by inactivation of Tis11 and Cth1 mRNA-binding proteins modulates replicative lifespan by increasing respiration due to elevated levels of mRNAs that are normally targeted by Tis11 and Cth1 for degradation, and that the mechanisms of lifespan extension in these mutants are at least partially distinct.